Comparison in estimating the ability and accuracy of a knitted test according to two strategies (two-stage and multi-stage hierarchical) using modern measurement theory. - Dr. liqaa shamil khalaf (Journal of College of Education, 2024)
Abstract The current research aims to estimate ability and its aggregated accuracy according to a dual strategy (two-stage and multi-stage hierarchical) using measurement theory. To achieve the goal, the study follows scientific steps in the analysis of general ability prepared by (Advanced Educational Administration) and published by the Australian Council for Educational Research for the middle school stage, starting with Translating the exact instructions for the test from English to Arabic and then performing a reverse translation. To verify the validity of the paragraphs of the expert experts for Iraqi work, they were presented to the two (10) experienced referees to know their opinions about the validity of the paragraphs and the amendments that were made to them. The researcher adopted a percentage Complete (100%) thus, the validity of the items was confirmed. The test was applied to a random sample of middle school students in the General Directorates of Education of Baghdad Al-Rusafa Governorate (1, 2, 3), numbering (400) male and female students. Statistical analysis of the items was conducted according to the single-teacher model using the statistical program. (bilog-mg3), and no items from the test were excluded, and it turned out that all items of the tool conform to the single model After that, the two-stage design was designed into two stages with the participation of the first stage (pre-test), consisting of (10) paragraphs. dations and proposals. Of (five sub-tests) divided according to the difficulty parameter, as for the (multi-stage hierarchical strategy), it was designed into (15) sub-tests divided according to the difficulty parameter. The tests were distributed into five stages in a hierarchical manner and the number of sub-tests is identical to the test stage. The first stage includes One test, the second stage includes two tests, the third stage includes three tests, the fourth stage includes four tests, and the fifth stage includes five tests distributed according to difficulty, After that, the two strategies were applied to a sample of (100) male and female students from schools affiliated with the First Rusafa Soil Directorate. Then each strategy was analyzed separately to extract the ability estimate, and then a comparison was made between the ability estimate and its accuracy for the two strategies (two-stage/multi-stage hierarchical) using the test. The results showed that there are no statistically significant differences between the two strategies in estimating ability, but there are statistically significant differences in the accuracy of the estimation (standard error) in favor of the multi-stage hierarchical strategy.